Human Adenomyosis Endometrium Stromal Cells Secreting More Nerve Growth Factor: Impact and Effect. (September 2015) - Li, Yan; Zou, Shien; Xia, Xian; Zhang, Shaofen
Abnormal expression of nerve growth factor (NGF) was found in adenomyosis (AM). We collected AM foci from patients and eutopic endometrium from non-AM controls. Endometrium stromal cells (ESCs) were cultured. Different levels of 17β-estradiol, tumor necrosis factor (TNF), CoCl2, and H2 O2 were added to the culture system separately, then the expression level of NGF in ESCs was detected. After adding different levels of NGF, the proliferation and apoptosis of ESCs and aromatase expression were detected. We found that 17β-estradiol promoted NGF production in AM ESCs but not in control ESCs; TNF promoted NGF production in both AM and control ESCs; and CoCl2 inhibited NGF production in control ESCs, but had no effect in AM ESCs. Nerve growth factor promoted the proliferation and synthesis of aromatase in AM ESCs. In conclusion, locally increased estrogen levels and inflammation may cause increased NGF production in the uterus of patients with AM. Nerve growth factor stimulated the proliferation and increased aromatase expression of ESCs from AM foci, suggesting NGF might contribute to the pathology and etiology of AM.